Evaluation of oak acorn (Quercus coccifera) as untraditional energy feedstuff for complete substitution of corn grains in fattening rabbit ration - Nowar M.S.; Al Shawabkeh K.; Nissour H. (Rabbit production in hot climates, 1994)
The present study aimed at evaluating oak acorn (Quercus coccifera) as a new untraditional energy source ingredient in fattening rabbit diet to minimize the feed cost. In Jordan the naturally growing oak trees produced annually about 20,000 tons acorn (oak fruits). This study aimed at evaluating acorn as untraditional feed for complete substitution of imported yellow corn grains in feeding rabbits. Two fattening rabbit rations were formulated and were identical in type and percentages of their ingredients, except one contained yellow corn grains and the second contained oak acorn. Each ration fed to 20 male 7 weeks-old Bauscat rabbits. Feeding oak acorn had no significant effects on rabbit performance carcass weight, internal organs, blood constituents and liver and kidney functions. Acorn also improved feed, protein and economic efficiencies. Results revealed that acorn could be considered as a new energy source and a replacer for imported yellow corn grain in feeding fattening rabbits. Further study to evaluate the fractions of CP and CF of acorn is needed.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)